Use of non-steroidal anti-inflammatory drugs in the prevention of Alzheimer‘s disease in the high risk patient - Li, Qinglu Chinglu (DALHOUSIE MEDICAL JOURNAL, 1997)
<!–[if gte mso 9]> <![endif]–><p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; tab-stops: 28.3pt 56.65pt 85.0pt 113.35pt 141.7pt 170.05pt 198.4pt 226.75pt 255.1pt 283.45pt 311.8pt 340.15pt; mso-layout-grid-align: none; text-autospace: none;">Alzheimer's disease (AD) is a major neurological disorder causing dementia in the elderly. Because the causes of AD are not known, there is no real treatment for this disorder. However, a number of risk factors have been associated with AD. Among these factors, a family history of AD is most significant. An inverse association between non-steroidal anti-inflammatory drugs (NSAIDs) use and AD has been previously demonstrated in several epidemiological studies. Here the potential use of NSAIDs as a protective measure for individuals in high risk groups is suggested. <!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>